Frog Virus 3 DNA Replication Occurs in Two Stages - Goorha, R. (1982)
Viral DNA synthesis in frog virus 3 (FV3)-infected cells occurs both in the nucleus and in the cytoplasm (Goorha et al., Virology 84:32-51, 1978). Relationships between viral DNA molecules synthesized in these two compartments and their role in the virus replication were examined. The data presented here suggest that (i) FV3 DNA replicated in two stages and (ii) nucleus and cytoplasm were the sites of stages 1 and 2 of DNA replication, respectively. Stages 1 and 2 were further distinguished by their temporal appearance during infection and by the sizes of the replicating DNA as determined by sedimentation in neutral sucrose gradients. In stage 1, replicating molecules, between the size of unit and twice the unit length, were produced early in infection (2 h postinfection). In contrast, stage 2 of DNA replication occurred only after 3 h postinfection, and replicating molecules were large concatemers. Results of pulse-chase experiments showed that the concatemeric DNA served as the precursor for the production of mature FV3 DNA. Denaturation of concatemeric DNA with alkali or digestion with S1 nuclease reduced it to less than genome size molecules, indicating the presence of extensive single-stranded regions. Analysis of replicating DNA by equilibrium centrifugation in CsCl gradients after a pulse-chase suggested that these single-stranded regions were subsequently repaired. Based on these and previous data, a scheme of FV3 replication is presented. According to this scheme, FV3 utilizes the nucleus for early transcription and stage 1 of DNA replication. The viral DNA is then transported to the cytoplasm, where it participates in stage 2 DNA replication to form a concatemeric replication complex. The processing of concatemers to produce mature viral DNA and virus assembly also occurs in the cytoplasm. This mode of replication is strikingly different from any other known DNA virus.